Ways to Adapt Foreign Fitness Terms in Armenian Language - Saghatelyan, Rita (Bulletin of Yerevan University B: Philology, 2025)
This article explores various methods of full Armenianization and positioning of the terms related to the modern fitness industry within the Armenian language. In this context, we aim to create Armenian equivalents for certain terms based on the general development trends of the language. We hope that through consistent and long-term usage, the most effective variants of these terms will become more recognizable. When developing Armenian equivalents for foreign fitness terms, we relied on the Armenian translation of terms related to the muscular system and parts of the human body, as these serve as the foundation of modern fitness vocabulary. In other words, the Armenian equivalents of contemporary fitness terms are primarily based on the precise translation of English terms related to the human muscular system. Many modern fitness terms originate from English descriptions of various movements, postures, and body positions. Therefore, we paid special attention to accurately translating these words into Armenian. In adapting these terms, we employed both calques and semi-calques. We considered another approach to Armenianization of fitness vocabulary – semantic expansion, as hundreds of colloquial expressions commonly used in fitness have evolved into the specialized terms over time. We also studied the experience of the Russian language, where, unlike in Armenian, fitness terminology is already well-established.